Cross-cultural training, expatriate self-efficacy, and adjustments to overseas assignments: an empirical investigation of managers in Asia. - Osman-Gani, Aahad M.; Rockstuhl, Thomas (Elsevier journal, 2009)
This paper presents the findings of an empirical study that investigated the relationship between cross-cultural training (CCT) effectiveness, self-efficacy, and adjustment of expatriate managers in Asia. Responses of 169 managers from four different national backgrounds, all currently on overseas assignments in Asia, indicate that the relationship between CCT effectiveness and adjustment is mediated by an increase in self-efficacy. Implications of the findings for professional practice and for future research are discussed